1996
DOI: 10.1007/bf00025418
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chlorella growth by the lipids of cyanobacterium Microcystis aeruginosa

Abstract: The total lipids of the cyanobacterium Microcystis aeruginosa have been isolated and fractionated into its components. Of these lipid components, only the fatty acid-containing fraction inhibited the growth of the green alga Chlorella pyrenoidosa . The inhibitory activity appears to be due to linoleic and linolenic acids, which are both present in significants quantities . These acids may be the substances responsible for the reported toxicity of Microcystis aeruginosa to Chlorella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…1998; Ikawa et al, 1996;Morohashi et al 1991 . Based on the results obtained from the present and previous studies, the activity of unsaturated fatty acids to mosquito larvae may be derived from the inhibition of Na q rK q -ATPase.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1998; Ikawa et al, 1996;Morohashi et al 1991 . Based on the results obtained from the present and previous studies, the activity of unsaturated fatty acids to mosquito larvae may be derived from the inhibition of Na q rK q -ATPase.…”
Section: Discussionmentioning
confidence: 98%
“…Unsaturated fatty acids extracted from Aphanizomenon flos-aquae and Microcystis aeruginosa inhibit the growth of the green Ž . algae Chlorella Ikawa et al, 1996 . Furthermore, fatty acids from Microcystis aeruginosa had shown the potential to inhibit potently fish gill Na q rK q -ATPase activ-Ž .…”
Section: Discussionmentioning
confidence: 99%
“…M. aeruginosa was shown to allelopathically inhibit the growth of Chlorella pyrenoidosa by linoleic and linolenic acids (Ikawa et al, 1996) and the freshwater dinoflagellate Peridinium gatunense (Sukenik et al, 2002). Also Harrass et al (1985) and Gregor et al (2008) When tested without interaction (100%), particle-, biovolume-, and chl a-based growth rates of M. aeruginosa were not affected or even slightly enhanced (chl a) by TA in exp.…”
Section: F=6mentioning
confidence: 99%
“…Direct competition for nutrients also occurs between cyanobacteria and eukaryotic algae. Ikawa et al (1996) found that unsaturated fatty acids purified from the cyanobacterium Aphanizomenon flos-aquae inhibited the growth of Chlorella. These findings do suggest that unsaturated fatty acids could be used by cyanobacteria to outcompete sympatric organisms.…”
Section: Potential Roles Of Unsaturated Fatty Acids In Cyanobacteriamentioning
confidence: 99%